Dalhuisen on transnational and comparative commercial, financial and trade law. Volume 1, The transnationalisation of commercial and financial law : the new Lex Mercatoria and its sources - Dalhuisen, J. H. (Jan Hendrik) (London [England] : Hart Publishing, 2022)
"This is a big book, with big themes and an author with the necessary experience to back them up... Full of insights as to the theories that underlie the rules governing contract, property and security, it is an important contribution to the law of international commerce and finance." ( Law Quarterly Review ) Volume 1 of this new edition covers the roots and foundations of private law, the different origins, structure, and orientation of civil and common law, and the social and cultural forces behind it. It analyses the practical needs and market forces behind the emergence of a new transnational commercial and financial legal order, its international finance-driven impulses, concepts, and operation; the theoretical basis of the transnationalisation of the law in the professional sphere in that order; the autonomous sources of the new law merchant or modern lex mercatoria derived from the method of public international law, as well as its relationship to domestic and transnational public policy and public order requirements. The complete set in this magisterial work is made up of 6 volumes. Used independently, each volume allows the reader to delve into a particular topic. Alternatively, all volumes can be read together for a comprehensive overview of transnational comparative commercial, financial and trade law."--
1. The Emergence of the Modern Lex Mercatoria , its Method, Structure and Antecedents. Civil or Common Law Thinking 1.1 Introduction 1.2 The Origin of Civil Law. Its Traditional Approach to Law Formation and to the Operation of Private Law. Effect on Commercial and Financial Law 1.3 The Origin and Evolution of the Common Law. Its Approach to Law, Private Law Formation and Operation 1.4 The Sources of Law in the Civil and Common Law Tradition. The Approach in Transnational Private Law and the Hierarchy of Sources of Law and Their Norms in the Modern Lex Mercatoria 1.5 Different Legal Orders, Their Manifestation, and the Competition Between Them. Cultural, Sociological and Economic Undercurrents in the Formation of Transnational Commercial and Financial Law (Modern Lex Mercatoria ) -- 2. The Nature, Status and Function of Private International Law 2.1 Modern Private International Law 2.2 The Modern European and US Approaches to Conflicts of Law 2.3 Interaction of Private International Law and Uniform Law -- 3. The Substance and Operation of Transnational Commercial and Financial Law or the Modern Lex Mercatoria 3.1 The Lex Mercatoria , Interrelation with Private International Law, Legitimation 3.2 The Hierarchy of Norms from Different Legal Sources in the Modern Lex Mercatoria : Elaboration of the Positive Law 3.3 Operation of the Lex Mercatoria . Objections
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Contracts (International law); Property; Commercial law; Law; Electronic books